Plan de Negocio para el montaje del Club-Bar Maretto en el centro histórico de la ciudad de Santa Marta , Departamento del Magdalena (2022)
Currently consuming alcoholic beverages is a distraction and fun for society, it has become fashionable to go out on weekends to a pleasant place to share with your friends or partner, therefore, the purpose of this document is to create the assembly of a CLUB-BAR in the city of Santa Marta, which is focused on providing experience and pleasant moments. To begin with, this document implements a model associated with research guidelines for setting up a business for the sale of alcoholic beverages. As for the Amaretto club-bar, its projection is to be distinguished before the different establishments for its style of innovation, seeking to implement a business idea where you can find different types of alcoholic beverages, delicious flavored sodas, and caps, of the same, There are spaces with different types of table games, with comfort, pleasant spaces and above all a good atmosphere to share in company. Regarding innovation management research, we seek to design a business model connoting a commercial, technical and financial study, developed a mixed typology, which addresses qualitative and quantitative scenarios of the research model.